Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/978-3-642-19423-8_34
|View full text |Cite
|
Sign up to set email alerts
|

A Collaborative Filtering Based Approach for Recommending Elective Courses

Abstract: In management education programmes today, students face a difficult time in choosing electives as the number of electives available are many. As the range and diversity of different elective courses available for selection have increased, course recommendation systems that help students in making choices about courses have become more relevant. In this paper we extend the concept of collaborative filtering approach to develop a course recommendation system. The proposed approach provides student an accurate pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 13 publications
0
22
0
1
Order By: Relevance
“…Loll and Pinkwart [15] employ collaborative filtering to score student assignment solutions based on peer evaluation, and show that it is as effective as manual assessment. Finally, similar to our work, Ray and Sharma [16] propose using collaborative filtering to predict student course grades. Our work differs from [16] in the following aspects:…”
Section: Related Workmentioning
confidence: 70%
See 2 more Smart Citations
“…Loll and Pinkwart [15] employ collaborative filtering to score student assignment solutions based on peer evaluation, and show that it is as effective as manual assessment. Finally, similar to our work, Ray and Sharma [16] propose using collaborative filtering to predict student course grades. Our work differs from [16] in the following aspects:…”
Section: Related Workmentioning
confidence: 70%
“…Finally, similar to our work, Ray and Sharma [16] propose using collaborative filtering to predict student course grades. Our work differs from [16] in the following aspects:…”
Section: Related Workmentioning
confidence: 70%
See 1 more Smart Citation
“…In [15] they narrated technical activity based course recommender system in which they defined an architectural model of this method using a collaborative filtering technique which is based on collecting and analyzing information about user activity.…”
Section: Related Workmentioning
confidence: 99%
“…Within the context of developing methods to predict the next-term grades, most existing approaches [4,7,8,19] rely on neighborhood-based collaborative filtering methods. For each student whose grade needs to be predicted, a set of similar students are identified that have already taken that course and their grades are used to estimate the desired grade via some similarity-weighted aggregation function.…”
Section: Related Workmentioning
confidence: 99%